Spirituality, Spiritual Values Treatment, and Firm Performance - Uno, Indra (Journal of Human Capital, 2008)
The purpose of this research paper is to explore the understanding and definition of spiritualityandspiritual values treatment to wards individual within an organization context. There have been researches that established positive correlation between workplace spiritualityand firm performance. However, many researches have been focused just on the concept and the correlation with firm performance rather than its implementation. As an intervention to an organization, spiritual values treatment has shown, at least anecdotally, to be a promising tool to improve firm performance. Perhaps such intervention as spiritual values treatment need to be furtherresearched in to and empirically tested to establish a positive correlation with firm performance. Keywords: Workplace Spirituality, Spiritual Values Treatment, Organizational Development